Challenges in Conducting MBBS Program in a Nepalese Medical College - Reddy, K Rajeshwar (Journal of Gandaki Medical College-Nepal, 2017)
The medical education in Nepal faces many challenges. Medical education, in order to keep up with the times, needs to adapt to the changing attitudes of society. We need a change for better. The curriculum is outdated to the clinical needs, and the students are rarely taught any skills and innovations or creativity to think for the future, and whoever wishes to change the system will be isolated. A serious shortage of talents, subject knowledge, technical skills and communication skills in teachers is affecting the future of medical students. Many medical teachers teach in local language making students poor communicators. Nepal, a developing country in South Asia is in transition had suffered from a decade long violent conflict and the country is in the implementation of its new constitution and suffers from political instability which may contribute several challenges like general shutdowns, frequent bandhs, shortage of electricity, load shedding, voltage fluctuation and problems with internet in conducting MBBS program in a Medical College. At the moment, there is no foreseeable future effort by parents, teachers, educationists, policy makers and politicians to correct this and courageously bring in radical reforms in medical education. These challenges can be overcome by cooperation and working together to create a peaceful and stable climate. Nepal has been going through tremendous changes in the last few years. Medical teachers have a great role to play and stand against many odds. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, Page: 49-56